2012
DOI: 10.1074/jbc.m111.320309
|View full text |Cite
|
Sign up to set email alerts
|

Structural Model of Channelrhodopsin

Abstract: Background:The channelrhodopsins are widely used for optogenetic application, whereas a structural model was not available before now. Results: Our modeled structure identifies remarkable structural motifs and elucidates important electrophysiological properties of Channelrhodopsin-2. Conclusion: Channel function relies on the unusual properties of helices 1 and 2. Significance: The atom level structure promotes further understanding of function and may guide the engineering of channelrhodopsins for novel opto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
60
0
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(68 citation statements)
references
References 49 publications
7
60
0
1
Order By: Relevance
“…In any case, anomalous shifts in the frequency of the C¼O stretch of carboxylic groups of proteins upon deuteration might indicate an unusual arrangement of H-bonds, whose characterization are best addressed by applying sophisticated quantum-mechanics/molecular-mechanics calculations (56,60,61). …”
Section: Discussionmentioning
confidence: 99%
“…In any case, anomalous shifts in the frequency of the C¼O stretch of carboxylic groups of proteins upon deuteration might indicate an unusual arrangement of H-bonds, whose characterization are best addressed by applying sophisticated quantum-mechanics/molecular-mechanics calculations (56,60,61). …”
Section: Discussionmentioning
confidence: 99%
“…An acidic residue at position 253 but not at position 123 is conserved in all ChRs sequenced so far (40). Whereas the replacement of D253 by nonprotonatable residues leads to the loss of channel function [D253A in C1C2 (6) and D253N in ChR2; SI Appendix, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…71 This experimental observation challenges the conclusions from an homology model of CrChR2 refined by QM/MM simulations, suggesting that cysteine residues showing notable vibrational changes in the S-H stretch could be H-bonded only at the sulfur atom. 74 Therefore, the observed 24 cm −1 downshift of the S-H band between the dark state and the P 2 380 state of CaChR1 must originate from an increase of the H-bond strength of the S-H group as a H-bond donor: from moderately to strongly H-bonded.…”
Section: F Hydrogen-bonding Changes Of the Thiol Group Of Cysteine Rmentioning
confidence: 99%
“…74,87 Consequently, a change in H-bonding strength of a cysteine side chain might originate either by a change in the pitch of the helix in the case of an intrahelical H-bond or a change in the relative orientation of two helices in the case of an interhelical H-bond. For CrChR2, it has been shown that the photocycle is associated with the movement of transmembrane helices, predominantly of helices B and F. 88 Because helix F of CaChR1 lacks cysteine residues, the cysteine residues in helix B (C133, C134, and C141) are prime candidates to undergo a measurable change in their S-H stretch frequency as a result of the structural changes.…”
Section: Hydrogen-bonding Changes In the Side Chain Of Internal Cymentioning
confidence: 99%
See 1 more Smart Citation